Sex Differences in Symptom Phenotypes Among Patients With Acute Myocardial Infarction - Brush, John E.; Krumholz, Harlan M.; Greene, Erich J.; Dreyer, Rachel P. (Circulation Cardiovascular quality and outcomes, 2020)
The diagnosis of acute myocardial infarction (AMI) is missed more frequently in young women than men, which may be related to the cognitive psychology of the diagnostic process. Physicians start the diagnostic process by intuitively recognizing familiar symptom phenotypes, but little is known about how symptoms combine in individuals as unique symptom phenotypes. We examined how symptoms of AMI combine as unique symptom phenotypes in individual patients to compare the distribution of symptom phenotypes in women versus men. The VIRGO study (Variation in Recovery: Role of Gender on Outcomes of Young AMI Patients) was a multicenter, observational cohort study of 3501 young adults hospitalized with AMI. Data were collected on presenting symptoms with standardized interviews and from medical record abstraction. The number and distribution of unique symptom phenotypes were compared between women and men. Because of the 2:1 female-to-male enrollment ratio, women and men were compared with permutation testing and repeated subsampling. There were 426 interview-symptom phenotypes in women and 280 in men. The observed difference between women and men of 146 phenotypes was significant, even allowing for the greater enrollment of women (permutation =0.004, median difference 110 under the null hypothesis of no association between sex and phenotype). The repeated subsample analysis also showed significantly more interview-symptom phenotypes in women than men (206.8±7.3 versus 188.6±6.0, <0.001). Women were more broadly distributed among symptom phenotype subgroups than men ( <0.001). Similar findings were observed in the analysis of symptoms abstracted from the medical record. Women exhibited substantially more variation in unique symptom phenotypes than men, regardless of whether the symptoms were derived from structured interviews or abstracted from the medical record. These findings may provide an explanation for the higher missed diagnosis rate in young women with AMI and may have important implications for teaching and improving clinicians' ability to recognize the diagnosis of AMI in women.